A Facile Strategy to Construct Amorphous Spinel‐Based Electrocatalysts with Massive Oxygen Vacancies Using Ionic Liquid Dopant. Issue 27 (6th August 2018) - Sun, Jing; Guo, Niankun; Shao, Zhiyu; Huang, Keke; Li, Yaowen; He, Feng; Wang, Qin
Abstract: Oxygen vacancies are demonstrated to be beneficial to various electrocatalytic reactions. However, integrating oxygen vacancies into an amorphous catalyst with a large specific surface area, and investigating its effect on the oxygen evolution reaction remains a great challenge. Herein, oxygen vacancies are introduced into an amorphous N, P, and F tri‐doped CoFe2 O4 using ionic liquid as a dopant. Simultaneously, ultrafine MoS2 nanoclusters are anchored onto its surface to increase the specific surface area. The vacancy‐rich MoS2 /NPF‐CoFe2 O4 exhibits an overpotential of 250 mV and a small Tafel slope of 41 mV dec −1, which is the best spinel‐based oxygen evolution reaction (OER) electrocatalysts so far. The excellent performance is attributed to massive oxygen vacancies, amorphous structure, large surface area, and synergistic coupling effects among active species. Density‐functional theory calculations reveal that the electronic structure of the catalyst can be modulated in the presence of heteroatoms and MoS2 nanoclusters, and then the energy barriers of intermediates are decreased as well, which enhances the OER performance. This design not only provides a simple strategy to construct amorphous structures with abundant oxygen vacancies using ionic liquid‐dopants, but also presents an in‐depth insight into the OER mechanism in alkaline solution. Abstract : Oxygen vacancies are introduced into an amorphous N, P, and F tri‐doped CoFe2 O4 using ionic liquid as dopant, and simultaneously ultrafine MoS2 nanoclusters are anchored onto its surface to increase the specific surface area. The as‐prepared vacancy‐rich hybrid exhibits superior catalytic performance toward the oxygen evolution reaction, which is the best spinel‐based OER electrocatalyst.